S. Jackson, P. Jansen, A. Mangoni (red.). Prescribing for Elderly Patients - Petrovic, Mirko (Tijdschrift voor Gerontologie en Geriatrie, 2012)
bespreking boekS. Jackson, P. Jansen, A. Mangoni (red.). Prescribing for Elderly Patients.-523 blz. Wiley-Blackwell, Chichester, 2009, ISBN 978-0-470-02428-7